2013
DOI: 10.1177/0013124513486289
|View full text |Cite
|
Sign up to set email alerts
|

Nearly 50 Years Post-Jim Crow

Abstract: This study addresses the segregation of English language learner (ELL) students in schools across Texas. We descriptively analyze levels of racial, economic, and linguistic isolation experienced by ELL students across the state of Texas. We also examine the association between segregation by race/ethnicity, economic disadvantage, and language proficiency with highstakes accountability ratings. Despite nearly two decades of accountability policies that have promised equality, our statistical analyses show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…One is the tendency of many people to conflate "desegregation" or "spatial mixing" with the more demanding conditions of true integration (Powell, 2005), which presumably would ensure real equality of opportunity. Several notable studies reveal that the desegregation, or the diversification of student populations, has led mainly to inequality of opportunity within schools (Carter, 2012;Hallinan & Williams, 1989;Lewis & Diamond, 2015;Merry, 2016;Tyson, 2011;Vasquez Heilig & Holme, 2013). Research in mixed schools and classrooms points toward differentiated treatment of teacher bias, stereotype threat, and lack of identity safety (Okonofua & Eberhardt, 2015; C. M. Steele, 1997;D.…”
Section: The Meso Dimensionmentioning
confidence: 99%
“…One is the tendency of many people to conflate "desegregation" or "spatial mixing" with the more demanding conditions of true integration (Powell, 2005), which presumably would ensure real equality of opportunity. Several notable studies reveal that the desegregation, or the diversification of student populations, has led mainly to inequality of opportunity within schools (Carter, 2012;Hallinan & Williams, 1989;Lewis & Diamond, 2015;Merry, 2016;Tyson, 2011;Vasquez Heilig & Holme, 2013). Research in mixed schools and classrooms points toward differentiated treatment of teacher bias, stereotype threat, and lack of identity safety (Okonofua & Eberhardt, 2015; C. M. Steele, 1997;D.…”
Section: The Meso Dimensionmentioning
confidence: 99%
“…Yet this belief is difficult to reconcile with virtually everything empirical research has reported for the past several decades (Coleman, 1966; Downey & Condron, 2016) concerning structural inequality, which, most studies continue to show, is prevalent in school systems in most countries to one degree or another (Domina et al, 2019; Schmidt et al 2015; Shavit & Blossfeld, 1993; Van de Werfhorst, 2019). Even in schools exhibiting “economic and racial balance” there is very little evidence to support the claim that either peer groups or high school classrooms are very heterogeneous with respect to race/ethnicity, social class background or ability, no matter how mixed the school population as a whole might be (Angrist & Lang, 2004; Conger, 2005; Darity & Jolla, 2009; Fiel, 2013; Vasquez-Heilig & Holme, 2013).…”
Section: Difficulties With the Integration Narrativementioning
confidence: 99%
“…Utilizing the SPSS recode variable feature, we aggregated students in each school into categorical variables denoting school-level non-White majorities (i.e., 99%-100% non-White, 90%-90% non-White, etc.). We used [5,49] to define the term intense segregation as 90% or more non-White in a school.…”
Section: Descriptive Analysesmentioning
confidence: 99%